The Effect of Promotion and Price on Purchase Decisions - Ade Yusuf; Denok Sunarsi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
The progress of a business is closely related to business management, while the rate of growth of a company is influenced by many things such as product development, sales concepts, and marketing concepts, therefore the sales concept and marketing concept are inseparable from promotional activities. Promotional activities are activities to promote goods directly to attract prospective buyers to the products being promoted Along with the advancing development of the era of the need for fashion has become a separate requirement for the community at large. And for products sold by PT. This study aims to determine the effect of promotion and price on purchasing decisions at PT. Total Creation. The method used was explanatory research with a sample of 96 consumers. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study have a significant effect on the promotion of purchasing decisions by 41.1%, hypothesis testing obtained significance 0,000 <0.05. Price significantly influence the purchase decision of 42.4%, the hypothesis test obtained significance of 0,000 <0.05. Promotion and price simultaneously have a significant effect on purchasing decisions of 51.9%, hypothesis testing obtained significance of 0,000 <0.05.